Validitas konstruk Inventori Adaptasi Inovasi Kirton dalam Bahasa Indonesia - Tobing, Gracia; Angelina, Veronika Efata; Franceline, Dea; Anwar, Morina Yuandary; Suwartono, Christiany; Halim, Magdalena (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
Every human is a problem solver. Humans always have to deal with different kinds of problems that needs to be resolved. We have our own way to solve our problem even if they face the same one. This is because humans have different cognitive style. How a person sees and solves his/her problems shows their cognitive style. The way we solve a problem is also can be an indicator of how creative a person is. Kirton’s Adaption-Innovation (KAI) Inventory was created to measure creativity style. This research was dedicated to adapt into Indonesian version of KAI Inventory. We used convenience sampling method and got 164 participants. We did measurement model for the conirmatory factor analysis. Then the psychometric tests have been done to ensure its reliability and validity. Based on the results of Inter-item Correlation, Correlation With Another Tests method, and Factor Analysis showed that Indonesian version of KAI Inventory was reliable but still needs some revision on its items to increase its validity.